Bimbingan dan Penyuluhan Inovasi Media Pembelajaran untuk Guru-Guru SMP Se-Komisariat Telukjambe Karawang - Sutirna; Suntoko; Beben Zuber Effendi; Umar Mukhtar; Yayah Nurasiah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The purpose of this service activity is to provide motivation with the aim of relying on boring, tedious, and frightening learning methods through the total use of internet-based learning media. The technique of enforcing network provider is withinside the shape of Work Shop Guidance and Counseling on Learning Media Innovations for Teachers on the Telukjambe Karawang Commissariat. The topics of the provider had been the lecturers of the Public and Private Middle Schools of the Telukjambe Commissariat, Karawang Regency. The provider tool used is a questionnaire approximately motivation in enforcing using net media as an innovation in gaining knowledge of. The effects of this provider had been obtained, namely (1) The belief of instructors in developing gaining knowledge of media turned into commonly very enthusiastic, however wished the guide of centers and infrastructure, (2) The motivation for innovation of instructors in developing gaining knowledge of media turned into very enthusiastic, (3) The motivation to put into effect the coaching and gaining knowledge of method via gaining knowledge of media improvements, it seems that nearly 1/2 of of them said that they had been prepared to perform improvements withinside the gaining knowledge of method, and (4) the incentive for gaining knowledge of improvements to be made into medical writings, evidently this nevertheless has a tendency to now no longer but provide an positive signal.